SUPERFÍCIES FRIAS - AVALIAÇÃO DA REFLETÂNCIA EM QUATRO CIDADES BRASILEIRAS APÓS UM ANO DE ENVELHECIMENTO NATURAL - Shirakawa, Márcia Aiko; Silva Junior, João Athaydes; Marques, Shirlei A. Vieira; John, Vanderley Moacyr (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The urban heat islands occur in the centers of big cities. The studies and actions to mitigate the urban heat islands have progressed in the last three decades, and the technologies of cool surfaces, with high reflectance and emitance, have gained international relevance, since the cool surfaces can reduce the consumption of energy for air conditioning. Reduction of reflectance can be caused by deposition of air pollutants, dusts and microbial growth according to environmental conditions. This study shows the loss of reflectance of an exposed white paint after one year in different cities: São Paulo, SP, Pirassununga, SP, São Sebastião, SP and Belém, PA. The results showed after one year the importance of microbial colonization in the loss of reflectance, mainly by phototrophic microorganisms. Studies are ongoing and assessments will be carried out for at least three years of exposure.